2020
DOI: 10.1016/j.heliyon.2020.e05075
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Pratylenchus brachyurus under dry soil conditions

Abstract: Pratylenchus brachyurus , a root-lesion nematode, depends on host plants for growth and survival. Weeds, volunteer plants, and crop root residues may act as reservoirs for the parasite in the field, but little is known about the ability of P. brachyurus to survive in the absence of a host. This study aimed to evaluate P. brachyurus survival and infectivity in artificially and naturally infested soil under dry conditions. Two experiments were conducted, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Unlike J4, which is resilient, the other forms of the parasite are sensitive to changes in soil moisture. Eggs, on the other hand, survive changes better than motile forms of the parasite [85]. In addition to withstanding dry soil, these can also survive freezing as anhydrobionts.…”
Section: Root-lesion Nematodes (Pratylenchus Spp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike J4, which is resilient, the other forms of the parasite are sensitive to changes in soil moisture. Eggs, on the other hand, survive changes better than motile forms of the parasite [85]. In addition to withstanding dry soil, these can also survive freezing as anhydrobionts.…”
Section: Root-lesion Nematodes (Pratylenchus Spp)mentioning
confidence: 99%
“…The loss of water from their bodies reduces the formation of ice needles that can pierce internal organ cells [86]. Although the reproductive capacity is not affected by anhydrobiosis, the reserve lipid content is managed differently during this stage, since it has been shown that lipid consumption is higher in females than in males [85,87].…”
Section: Root-lesion Nematodes (Pratylenchus Spp)mentioning
confidence: 99%
“…Previous works have studied how water stress affects the host response in different crops to plant-parasitic nematodes, such as Meloidogyne [40][41][42][43], Heterodera [44], and Praty-lenchus [41,45]. These studies have shown how water stress is, in most cases, a relevant factor in reducing the general development of plants, also negatively affecting nematode reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Entrar em estado de dormência, anidrobiose, é outra forma de sobrevivência do nematoide em condições adversas (Perry;Moens, 2006). Ribeiro et al (2020) conduziram estudos com intuito de analisar a capacidade de sobrevivência de P. brachyurus em condições de solo seco e, observaram que a permanência de raízes no campo favoreceu a multiplicação do patógeno comparado a solos sem hospedeiros, além de manter a sua infectividade por cerca de 90 dias.…”
Section: Pratylenchus Brachyurusunclassified